2018
DOI: 10.3389/fmicb.2018.02248
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Toxins of Vibrio Pathogens and Their Role in Epithelial Disruption During Infection

Abstract: Gastrointestinal episodes associated with Vibrio species have been rising worldwide in the last few years. Consequently, it is important to comprehend how occurs the production of diarrhea, to establish new preventive and therapeutic measures. Besides the classical CT and TCP toxins, Zot, RTX, and Ace among others have been deeply studied in V. cholerae. However, in other Vibrio species of clinical interest, where some of these toxins have been reported, there is practically no information. Zot activates a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 96 publications
0
50
0
Order By: Relevance
“…For instance, CTXΦ is able to transduce the cholera toxin (CT) from V. cholera to V. mimicus leading to the emergence of a pathogenic V. mimicus form (58, 59). Many vibriophages contain virulence genes responsible for severe gastro-intestinal diseases (47, 48). For instance, almost 80% of clinical V. parahaemolyticus strains contain filamentous phages, encoding the zona occludens toxin (Zot) (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CTXΦ is able to transduce the cholera toxin (CT) from V. cholera to V. mimicus leading to the emergence of a pathogenic V. mimicus form (58, 59). Many vibriophages contain virulence genes responsible for severe gastro-intestinal diseases (47, 48). For instance, almost 80% of clinical V. parahaemolyticus strains contain filamentous phages, encoding the zona occludens toxin (Zot) (22).…”
Section: Discussionmentioning
confidence: 99%
“…We found that one of the active filamentous phages (i.e. Vibrio phage VALGΦ6) contains the virulence cassette comprising the Zot and the Ace proteins, which is frequently found in vibriophages and responsible for severe gastro-intestinal diseases (47, 48). To compare these two proteins with other Zot and Ace proteins isolated from various vibriophages we generated protein alignments using AliView (40) and examined the presence of Walker A and Walker B motifs in Vibrio phage VALGΦ6 Zot proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The gut lumen contains 10 3 -10 11 bacteria/ml, [63] that in aggregate contain 1 g or more of endotoxin, that if purified and intravenously injected could be fatal to hundreds or even thousands of humans [64]. Endotoxins activate specific membrane receptors termed Toll-like receptors that are members of a class of pro-inflammatory receptors hat recognize pro-inflammatory molecules termed "patternassociated molecular patterns" or PAMPS that in turn can activate genes that initiate inflammatory cascades in the host [49,65]. Parenteral administration of minute amounts of endotoxins to humans elicits an inflammatory reaction typical of SIRS (fever or hypothermia, tachycardia, hyperpnea, leukocytosis, and hypotension), whereas larger amounts of administered endotoxins typically produce sepsis and shock [66,67].…”
Section: Pathologic Consequences Of Bt and Endotoxin Transportmentioning
confidence: 99%
“…This is a pentameric toxin that triggers signals for elevation of intracellular cAMP and consequently, stimulates luminal secretion of electrolytes and water from enterocytes. This is the basis of loss of water and electrolytes from the gut, weight loss, dehydration and death [46,47].…”
Section: Amongmentioning
confidence: 99%
“…Furthermore, the intestinal cells are stimulated by the Accesory cholera enterotoxin (ACE), to secrete Ca 2+dependent Cl -/HCO3 -, while the Heat stable enterotoxin (Sta) causes increased cGMP secretion and inhibition of the regulatory mechanism of Na + /Cl. These thus lead to an efflux of water and electrolytes (sodium and chloride ions) into the gut lumen, causing the profuse watery diarrhoeal characteristic seen in cholera disease [46].…”
Section: Cholera Toxin (Choleragen) and Its Mechanism Of Actionmentioning
confidence: 99%